Dramatic transfers: Mural painting and religious theatre in the Western Alps during the sixteenth century (Theatrum historiae, 2021)
In the specific context of the late medieval Alps, it has been demonstrated that artistic exchanges and the circulation of iconographic and stylistic patterns were quite common. Transference can take place between different media, like religious theatrical mysteries and painted works of art such as alpine chapels’ wall paintings. This paper explores the circulation of theatrical mysteries through the Alps between Provence, Brianzonese and Piemonte. It analyses some examples of iconographic transference, like composition, precise gesturing, attributes and accessories but also characters designation. A series of accurate matches is thus selected in vices and virtues wall paintings and in some saints’ painted cycles. It demonstrates also correspondences in the expressionism and dolorism in some episodes of saint Anthony’s life. With the analysis of two saints’ cycles (saints Andrew and Bartholomew), it will conclude trying to explain how to find the presence or the absence of dialogue between religious mysteries and wall paintings.
Keywords: mystery plays; wall paintings; visual studies; iconography; devotion